Inductive reasoning renewed: a reply to commentators - Krueger, Joachim I.; Grüning, David; Heck, Patrick; Freestone, David (Psychological inquiry, 2024)
The IRM provides a simple and flexible framework for the study of the social-perceptual phenomena of self-enhancement, intergroup accentuation, ingroup-favoritism, and differential accuracy of group perception, as well as the interdependencies of these phenomena. The commentaries on the target article (Krueger and colleagues) point to opportunities to further develop the model and to situate it in the context of contemporary theory and research in social and cognitive psychology. We address several critical issues of concern in this rejoinder. We organize our arguments along four themes of discussion: the model’s coherence, validity, sufficiency, and its timeliness. We close by suggesting that the IRM, beyond its proper domain of applicability represents a way of thinking about social perception characterized by parsimonious assumptions and precise predictions.